The Effect of Educational Technology on EFL Learners’ Self-Efficacy - Zhang, Ying (Frontiers in Psychology, 2022)
This paper aimed at investigating the related studies on educational technology and its effect on English as a Foreign Language (EFL) learner self-efficacy. Earlier studies have proved the positive and significant relationship between learner self-efficacy and educational technology use. Investigations have revealed that improving learners’ dynamic mindsets, online interaction, self-assessment, academic knowledge, and positive affectivity can increase learner self-efficacy. Moreover, the provision of encouraging context can help develop learners’ self-efficacy in technology-supported education. Furthermore, the study presented the implications and future directions of this line of research for different people, such as EFL teachers, teacher educators, and foreign language scholars. The ideas can improve their awareness of learner self-efficacy in technology-supported educational contexts and its role in L2 education.